2021
DOI: 10.1111/imm.13367
|View full text |Cite
|
Sign up to set email alerts
|

The detection of long‐lasting memory foot‐and‐mouth disease (FMD) virus serotype O‐specific CD4+ T cells from FMD‐vaccinated cattle by bovine major histocompatibility complex class II tetramer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…We noticed that even within the cytokine producing T cell population, the CD45RA/RO expression pattern was associated with distinct T cell subtypes, which is in agreement with several previous reports. It has been reported that the antigen-specific memory CD4+ population is within the CD45RO+ population [ 5 , 8 , 23 , 24 , 38 , 39 ], but that of CD8+ T cells contains both CD45RA+ and CD45RO+ fractions [ 8 , 34 , 35 , 37 ]. Previously, cytokine-producing ovalbumin (OVA)-specific memory bovine CD4+ T cells were found within the CD45RO+ sub-population, which is in line with another report, where the CD45RO+ fraction of the CD4+ T cells dominantly produced IFN-γ and IL4 in both blood and lymph nodes [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed that even within the cytokine producing T cell population, the CD45RA/RO expression pattern was associated with distinct T cell subtypes, which is in agreement with several previous reports. It has been reported that the antigen-specific memory CD4+ population is within the CD45RO+ population [ 5 , 8 , 23 , 24 , 38 , 39 ], but that of CD8+ T cells contains both CD45RA+ and CD45RO+ fractions [ 8 , 34 , 35 , 37 ]. Previously, cytokine-producing ovalbumin (OVA)-specific memory bovine CD4+ T cells were found within the CD45RO+ sub-population, which is in line with another report, where the CD45RO+ fraction of the CD4+ T cells dominantly produced IFN-γ and IL4 in both blood and lymph nodes [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selective detection of CD45RO transcript by quantitative PCR (qPCR) is not practical. Instead, due to the highly conserved nature of CD45 protein across the mammalian species [ 28 , 31 ], bovine CD45RO expression is commonly examined at the protein level using a monoclonal antibody (clone # ILA116) in flow cytometry [ 5 , 8 , 24 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Bembridge et al (1995) in their seminal research first used this monoclonal antibody (clone #ILA116) to precipitate bovine CD45RO, which had a molecular weight very close to that of humans (180 kDa), and suggested that this isoform could be associated with memory [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial research in humans suggested that expression of CD45RA marks the naïve, and that of CD45RO indicates memory T cells (Akbar et al 1988a, Merkenschlager et al 1988, Richards et al 1990, Wallace and Beverley 1990, Litjens et al 2008, Machura et al 2008, which was similarly established in cattle soon after (Howard et al 1991;Bembridge et al 1995). Although how CD45RO is spliced in cattle is unknown, a protein of a molecular weight similar to that in humans (i.e., 180 kDa) was precipitated (Bembridge et al 1995), using the most popular monoclonal antibody clone IL-A116 (Bembridge et al 1995;Ballingall et al 2001;Endsley et al 2006;Denis et al 2011;Hogg et al 2011;Blunt et al 2015;Maggioli et al 2015;Frie et al 2017;Elnaggar et al 2021;Jonsson et al 2021;Mitoma et al 2021). Similarly, there are ten monoclonal antibodies that recognize the high molecular weight isoform in cattle (Dutia et al 1993, Howard andNaessens 1993); among them, clones CC76 and GC6A have already been applied to detect the bovine homologue of CD45RA (Endsley et al 2007;Denis et al 2011;Kandel et al 2022).…”
Section: Alternative Splicing Generates Cd45ra/ro In Humansmentioning
confidence: 99%
“…Therefore, detection of memory T cells is the gold standard for analyzing the efficacy of vaccines in humans and domestic animals like cattle (Flaxman and Ewer 2018). Currently, bovine memory T cells are detected as CD45RO + /CD45RA - (Howard et al 1991, Bembridge et al 1995, Sopp and Howard 2001, Silflow et al 2005, Maggioli et al 2015, Frie et al 2017, Mitoma et al 2021, which were adopted a few years after their initial establishment in humans (Akbar et al 1988a;Merkenschlager et al 1988;Terry et al 1988;Birkeland et al 1989;Deans et al 1989;Richards et al 1990). However, in the last two decades, reports contrasting initial observations have been published in both humans and cattle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation